Revolutionizing Learning: Unveiling the Influence of Liveworksheets Embedded within Contextual Teaching - Alfira, Alfira; Salmilah, Salmilah; Suryani, Lilis (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2024)
This study explores developing and implementing integrated teaching materials using Liveworksheets and a contextual approach to enhance learning processes in fourth-grade classrooms. Acknowledging the growing influence of technology in education, this research underscores the necessity for practical teaching resources that can enhance student engagement and comprehension. Employing the ADDIE model for its systematic development process, the study conducted a comprehensive analysis, design, development, implementation, and evaluation of the materials. Validation by expert reviewers in language, content, and design affirmed the materials' high validity, with scores between 94% and 95%. Practicality assessments involving 18 fourth-grade students and their teacher demonstrated the materials' effectiveness, achieving an efficient rating with an average score of 94.16%. The findings suggest that Liveworksheets-assisted teaching materials, enriched with a contextual approach, significantly contribute to a more interactive and understanding-focused learning environment. This study highlights the potential of digital tools in enhancing the educational experience, offering a valuable resource for educators seeking to incorporate technology into their teaching strategies.